The family Ascidiidae Herdman (Tunicata: Ascidiacea) in Bocas del Toro, Panama. Description of six new species - Bonnet, Nadia Y. K.; Rocha, Rosana M. (Zootaxa, 2011)
We have been collecting Ascidians in the Bocas del Toro region of Panama since August 2003, mostly in the mangroves but also in shallow coral reefs. Here we will describe six new species from this region (Phallusia fragilis, Ascidia bocatorensis, A. collini, A. corallicola, A. monnioti and A. panamensis), register and complement the description of an additional seven species in the family Ascidiidae (A. archaia, A. curvata, A. interrupta, A. cf. munda, A. sydneiensis, A. tenue and Phallusia nigra). We also provide a tabular identification key that also includes P. caguayensis and A. xamaycana. Most of the species are very abundant on mangrove roots.